Enhancing Speaking Skill By Utilizing Podcast Material for Teenager Learners - Laiel, Habib Alwi jamalul; Suseno, Edy (ELT Worldwide: Journal of English Language Teaching, 2023)
Speaking is a form of practicing how to communicate ideas. The students can convey their intentions by speaking. Many high school students struggled to articulate their thoughts. Their low vocabulary, pronunciation, and grammar skills are what cause it. The teacher employed podcast resources in the teaching-learning process to address these issues. The instructor went over the basic grammar to put it into practice. In order to make it stick in their minds, the teacher instructed the student to look for the corresponding grammar in the transcript. Then, in order to expand their vocabulary, the student translate it. To improve the students' listening abilities, an audio recording was employed. The transcript was then read aloud. The students' newly acquired information is put to use in the text and audio descriptions of the images. The students took a pre-test before beginning this treatment, and they finished a post-test at the conclusion of it. A mixed-method approach was used to analyze the data that was found. It may be inferred that using podcast content improved the students' speaking proficiency. This kind of research can be used byteachers to teach relevant subjects. It also motivates other scholars to conduct deeper investigation.